Short-chain fatty acids are potential goalkeepers of atherosclerosis - Feng, Yu; Xu, Danyan (Frontiers in Pharmacology, 2023)
Short-chain fatty acids (SCFAs) are metabolites produced by gut bacteria and play a crucial role in various inflammatory diseases. Increasing evidence suggests that SCFAs can improve the occurrence and progression of atherosclerosis. However, the molecular mechanisms through which SCFAs regulate the development of atherosclerosis have not been fully elucidated. This review provides an overview of the research progress on SCFAs regarding their impact on the risk factors and pathogenesis associated with atherosclerosis, with a specific focus on their interactions with the endothelium and immune cells. These interactions encompass the inflammation and oxidative stress of endothelial cells, the migration of monocytes/macrophages, the lipid metabolism of macrophages, the proliferation and migration of smooth muscle cells, and the proliferation and differentiation of Treg cells. Nevertheless, the current body of research is insufficient to comprehensively understand the full spectrum of SCFAs’ mechanisms of action. Therefore, further in-depth investigations are imperative to establish a solid theoretical foundation for the development of clinical therapeutics in this context.